Dinamika Hukum dan Politik dalam Dugaan Kasus Korupsi yang Melibatkan Pertamina: Analisis Yuridis dan Implikasinya terhadap Kebijakan Energi Nasional - Erick Darmansyah; Ariawan Gunadi (CV Rewang Rencang, 2024)
This study aims to analyze the legal and political dynamics in the alleged corruption case involving PT Pertamina and its implications for Indonesia’s national energy policy. The research method used is normative with statutory and case approaches. This case reveals the weakness oversight in energy governance, with indications of oil import manipulation and fuel adulteration. National political dynamics affect the independence of law enforcement processes, with potential interference from vested interests. These irregularities have wide-ranging effects on public trust, consumer protection, and national energy supply stability. The financial loss to the state is enormous, reaching hundreds of trillions of rupiah, alongside consumer losses due to substandard fuel products. Additionally, poor SOE governance underscores the urgency of reforming energy policy and strengthening oversight mechanisms. In conclusion, strategic measures are needed, including transparency, stronger law enforcement independence, and energy policy reform that serves the public interest.